ANALISIS RESTRUKTURISASI PEMBIAYAAN PERBANKAN SYARIAH DIMASA COVID-19 TAHUN 2020 - Dody Wijaya Hardi; Muhammad Ilham (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The COVID-19 outbreak that originated in Wuhanhas been declared a pandemic, not only affecting the health sectorbut also affecting other sectors that affect it. One of them is in thebanking business, as a result, many customers feel that theirbusiness is not running smoothly. The result is congestion inbanking activities. Thus, the government has provided a stimulus tocustomers through the POJK to provide relief in the financing,including sharia banking financing. This research is of courseincluded in the normative juridical research method withqualitative research types, as the main ingredient of course referringto POJK Number 11/POJK.03/2020 concerning National EconomicStimulus. Then added with secondary materials in the form of theCivil Code and PERMA. steps and strategies to save financing asan effort by sharia banks to improve the financing position andfinancial condition of customers by re-positioning the financingthrough contract renegotiation and refinancing in financingcontracts